MORPHOLOGICAL CHANGES DUE TO ANTHROPOGENIC INTERFERENCES IN GENDOL RIVER VALLEY, MERAPI VOLCANO - Malawani, Mukhamad Ngainul; Handayani, Tiara; Bariq, Jundi Muhammad; Lukafiardi, Radikal (Universitas Muhammadiyah Surakarta, 2019)
This research aims to identify the morphological changes in Gendol river, Merapi volcano. After the eruption 2010, Gendol river filled up by pyroclastic materials, then utilized as mining area. As the volcanic materials are abundance in Gendol river, sand mining activities are dominant, causing antrophogenic interferences that changes the morphology of Gendol valley. In this study, the morphological changes is measured by terrestrial survey, aerial mapping, and materials analysis through petrographic and granulometric analysis. Aerial mapping was conducted in February and August 2019 in order to identify the dynamic changes during 6 months observation. Vertical changes is found in the active mining zone, in western-side of research area, while horizontal changes was found in eastern-side. The comparison of widening and narrowing valley is 13:1 due to horizontal changes. Result of petrographic analysis showes that three different sampling locations originated from similar provenance, which is undissected arc provenance but may differ in period of sedimentation. Grain material found in research are categorized as suitable material for mining with the 0,733 mm grain size. However, the mining activities should be aware of material availability to minimize the riverbank failure.